If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5x + -6 = -7 Reorder the terms: -6 + 0.5x = -7 Solving -6 + 0.5x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 0.5x = -7 + 6 Combine like terms: -6 + 6 = 0 0 + 0.5x = -7 + 6 0.5x = -7 + 6 Combine like terms: -7 + 6 = -1 0.5x = -1 Divide each side by '0.5'. x = -2 Simplifying x = -2
| -10-7w=-4-6w | | 125=-.5x^2+25x-150 | | 2+9x=100 | | -49+10x-6x=43 | | -2.2+-8.9= | | x-4.5=12.01 | | h^2*j*k^3=343 | | 125(3x-2)=25(2x+1) | | 4p-8=4(p-2) | | 04x+3.9=5.78 | | 2(x+4)=2(x-1)+3 | | 13-6x=-5(x-4) | | 4-4n=-4(n-1) | | 15+23=k+30 | | X+56.3=44.6 | | 14x+11+25+90=180 | | 3x+5(2x+y)=0 | | F(a)=10x-2 | | 8.1+x=3.6 | | 12(x-6)=-8-4 | | 37+2g=87 | | 4-n=4(n-1) | | 4(3x+1)=5x-6 | | -5(1-4m)=6m+37 | | 180=5x+12+6x-10 | | -7p+5p=-3p-31 | | 70-30=10+ | | 4x-12+5x=-30 | | 4x^3-4x^2-224x=0 | | 50-40=10+ | | -3v-3=-21 | | 30x+5(2x+y)=0 |